STEAM to Protect: Cyberbullying Education and Children's Digital Rights in the Context of Citizenship Law at Giripurno Islamic Elementary School, Magetan - Prastyaningrum, Ihtiari; Mustikarini, Indriyana Dwi; Pratama, Nurmansa Willyam (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2025)
Bullying is a phenomenon that frequently occurs among children. It can happen directly or through digital platforms, commonly known as cyberbullying. Providing early education about cyberbullying is crucial. This education can be delivered through family-based learning or integrated into school activities. A collaborative approach that combines five disciplines-science, technology, engineering, art, and mathematics (commonly known as STEAM) can be an effective learning method to educate children about bullying and cyberbullying. Madrasah Ibtidaiyah Giripurno in Magetan is one of the elementary schools located in Magetan Regency. Based on observations and interviews with teachers, it was found that some students still engage in bullying behavior, such as giving hurtful nicknames or calling others by their father’s name. The challenge lies in how to provide meaningful education to students not just through lectures, but through active engagement so that students can develop a deeper understanding of the issue. In response to this, we collaborated with the Giripurno Community Service (KKN) Team and the teachers to design a thematic learning activity that incorporates all five STEAM disciplines, focusing on educating students about bullying, cyberbullying, and legal aspects of citizen rights protection. The activity included awareness sessions, group discussions, and hands-on practices such as anti-bullying campaigns. The results showed an improvement in students’ understanding of bullying and cyberbullying, how to use social media wisely, and how to protect their personal data on digital platforms. It is hoped that this program will help students become more confident and ensure that they refrain from bullying, considering its serious physical and psychological consequences.